Isolation and characterization of a perchlorate-reducing Acinetobacter bereziniae strain GWF. Issue 5 (2nd September 2016) - Zhang, Yuanyuan; Lu, Jianbo; Guo, Jianbo; Wang, Qian; Lian, Jing; Wang, Yajun; Zhang, Chao; Yang, Jingliang
ABSTRACT: A novel strain, Acinetobacter bereziniae strain GWF(KM062029), was isolated from anaerobic activated sludge. The complete 16S rDNA sequence showed that strain GWF has closest homology (100%) with A. bereziniae strain BENAB7 (HE651923.1) and A. bereziniae strain ATCC 17924 (HE651922.1). Strain GWF is a Gram-negative, non-fermentative facultative anaerobe. The optimum growth conditions were shown to be 30 °C, pH 7.5 and acetate-to-perchlorate ratio of 10, respectively. In this study, anthraquinone-1-sulfonate (α-AQS) was the best redox mediator in the perchlorate reduction, and the optimum concentration range was 1.067 mmol/L. The perchlorate reduction rate was enhanced 1.33-fold using 1.067 mmol/L α-AQS. Meanwhile, strain GWF could not withstand the effect of concomitant anions (nitrate, chlorate, chlorite). The concomitant anions constants were 30 mg/L and 1.0 mmol/L for nitrate and chlorate, respectively. Chlorite completely inhibited the perchlorate reduction, and the inhibition did not depend on the concentration of chlorite.